2012
DOI: 10.1002/mpr.359
|View full text |Cite
|
Sign up to set email alerts
|

Does cannabis onset trigger cocaine onset? A case‐crossover approach

Abstract: Psychiatric researchers tend to select the discordant co-twin design when they seek to hold constant genetic influence while estimating exposure-associated disease risk. The epidemiologic case-crossover research design developed for the past two decades represents a viable alternative, not often seen in psychiatric studies. Here, we turn to the epidemiologic case-crossover approach to examine the idea that cannabis onset is a proximal trigger for cocaine use, with the power of 'subject-as-own-control' research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…After all, for the most part, social sanctions against drug use might be considered to be shared aspects of the co-twin environment. Nonetheless, as noted elsewhere (O’Brien et al, 2012), even in research on cannabis-related outcomes of discordant monozygotic (MZ) co-twins, one must explain why one member of twin pair has consumed cannabis (or has consumed it earlier than the other co-twin) and why the other member of the twin pair has not done so. These observational designs also are subject to the challenge of uncontrolled confounding.…”
Section: Toward More Definitive Evidence On These Topicsmentioning
confidence: 98%
See 1 more Smart Citation
“…After all, for the most part, social sanctions against drug use might be considered to be shared aspects of the co-twin environment. Nonetheless, as noted elsewhere (O’Brien et al, 2012), even in research on cannabis-related outcomes of discordant monozygotic (MZ) co-twins, one must explain why one member of twin pair has consumed cannabis (or has consumed it earlier than the other co-twin) and why the other member of the twin pair has not done so. These observational designs also are subject to the challenge of uncontrolled confounding.…”
Section: Toward More Definitive Evidence On These Topicsmentioning
confidence: 98%
“…In some of our group’s work, and O’Brien et al (2012) have raised the possibility that the subject-as-own-control case-crossover design with epidemiological samples of individuals studied before and after onset of first drug use might help constrain the sources of individual-level variation more than would be the case in MZ co-twin designs of behavioral genetics. This point is made explicit in O’Brien et al (2012), where we goso far as to indicate that the epidemiological case-crossover design should be included more generally in any comprehensive coverage of informative behavioral genetics research approaches, designs, and methodology.…”
Section: Toward More Definitive Evidence On These Topicsmentioning
confidence: 99%
“…(Degenhardt et al, 2010 ;Ter Bogt, Schmid, Gabhainn, Fotiou et Vollebergh, 2006). Qui plus est, l'existence de mécanismes étiologiques partagés, à la fois génétiques et environnementaux, pour l'ensemble des troubles liés à l'utilisation de substances expliquerait vraisemblablement la concomitance fréquente de ces troubles (O'Brien, Comment, Liang et Anthony, 2012 ;van Leeuwen et al, 2011). De façon exploratoire, une récente étude américaine sur des individus âgés de 18 à 25 ans a mis en lumière une relation linéaire entre l'usage de cannabis et celui de substances illicites (opiacés, cocaïne, inhalants, hypnotiques).…”
Section: Troubles Liés à L'utilisation D'autres Substancesunclassified
“…However, even elegant methods such as the discordant twin design have their caveats. Recently, O’Brien and colleagues (91) concluded that the origins of twin discordance (for early onset cannabis use) are as pertinent as the sequelae of this discordance (e.g. other illicit drug use or low academic achievement).…”
Section: Considerations and Caveatsmentioning
confidence: 99%